2022
DOI: 10.3389/fimmu.2022.899932
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Endoscopic Skull Base Surgery: Another Treatment Option After Immunotherapy for Recurrent Nasopharyngeal Carcinoma

Abstract: BackgroundAdvanced recurrent nasopharyngeal carcinoma (NPC) is a relatively common nasopharyngeal skull base disease for which there is no uniform treatment modality. Not all patients are satisfied with the efficacy of immunotherapy with or without chemotherapy.MethodsThis study included patients who underwent salvage endoscopic skull base nasopharyngectomy after immunotherapy between February 2017 and June 2021. Patient survival information was analyzed. Relevant publications were retrieved from five database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
0
1
Order By: Relevance
“…A recent study reported that 9 patients with advanced rNPC who had not responded to immunotherapy received salvage skull base surgery. The 2-year OS and PFS rates were 25.0 and 29.2%, respectively [ 28 ], which are significantly lower than those in the immunotherapy group of our study (OS: 90.0%; DFS: 80.0%). This finding suggests that patients with advanced rNPC who receive postoperative consolidation immunotherapy may achieve better survival parameters than those who receive salvage ENPG after immunotherapy failure.…”
Section: Discussioncontrasting
confidence: 64%
“…A recent study reported that 9 patients with advanced rNPC who had not responded to immunotherapy received salvage skull base surgery. The 2-year OS and PFS rates were 25.0 and 29.2%, respectively [ 28 ], which are significantly lower than those in the immunotherapy group of our study (OS: 90.0%; DFS: 80.0%). This finding suggests that patients with advanced rNPC who receive postoperative consolidation immunotherapy may achieve better survival parameters than those who receive salvage ENPG after immunotherapy failure.…”
Section: Discussioncontrasting
confidence: 64%